Assignments across the curriculum: a national study of college writing - Melzer, Dan, author; Utah State University Press, publisher (Colorado State University. Libraries, 2014)
In Assignments across the Curriculum, Dan Melzer analyzes the rhetorical features and genres of writing assignments through the writing-to-learn and writing-in-the-disciplines perspectives. Presenting the results of his study of 2,101 writing assignments from undergraduate courses in the natural sciences, social sciences, business, and humanities in 100 postsecondary institutions in the United States, Assignments across the Curriculum is unique in its cross-institutional breadth and its focus on writing assignments. The results provide a panoramic view of college writing.
1. A Panoramic View of College Writing -- 2. Limited Purposes, Narrow Audiences: The Rhetorical Situations of College Writing -- 3. Social Action, Social Inaction: The Genres of College Writing -- 4. Each Course Is a Community: The Discourse Communities of College Writing -- 5. The Power of Writing across the Curriculum: Writing Assignments in WAC Courses -- 6. Implications for Teachers, Tutors, and WAC Practitioners -- Appendix A: Institutions Surveyed -- Appendix B: Sample Coded Assignments.
Keywords: English language -- Rhetoric -- Study and teaching; Report writing -- Study and teaching